2006
DOI: 10.1016/s1449-4035(06)70074-1
|View full text |Cite
|
Sign up to set email alerts
|

Discourse in Comparative Policy Analysis: Privatisation Policies in Britain, Russia and the United States

Abstract: Privatisation has been of the most widely used and extensively debated policies in the world for the last quarter century. This phenomenon, though, is mostly unified by rhetoric, and substantially varies across time and space, particularly in implementation. To answer the question of what presupposes a choice of particular mechanism of privatisation, three distinct cases of privatisation (the US, the UK, and Russia) are analysed through Fischer's (1995) model of practical policy deliberation. The model tests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…This was primarily because of the importance of large facilities that could enable the storage of large quantities of water throughout the dry season and which can ensure an optimum and adequate supply of sustainable safe water in households. At the same time, in local or intemational marketplaces, water is traded in large quantities as a commodity to augment national or household consumption needs and, in some countries, the supply of water is privatised to improve delivery (Gabrielyan, 2006;Marques, 2006;Hall & Lobina, 2007;Kazimbaya-Senkwe & Guy, 2007;Botto et al, 2011). This study found tank size to be statistically significant.…”
Section: Discussionmentioning
confidence: 69%
“…This was primarily because of the importance of large facilities that could enable the storage of large quantities of water throughout the dry season and which can ensure an optimum and adequate supply of sustainable safe water in households. At the same time, in local or intemational marketplaces, water is traded in large quantities as a commodity to augment national or household consumption needs and, in some countries, the supply of water is privatised to improve delivery (Gabrielyan, 2006;Marques, 2006;Hall & Lobina, 2007;Kazimbaya-Senkwe & Guy, 2007;Botto et al, 2011). This study found tank size to be statistically significant.…”
Section: Discussionmentioning
confidence: 69%